2000
DOI: 10.1159/000010241
|View full text |Cite
|
Sign up to set email alerts
|

Stress Vulnerability and Climacteric Symptoms: Life Events, Coping Behavior, and Severity of Symptoms

Abstract: To explore a possible association between climacteric symptoms and ways of coping with stress, a comparative study was conducted among 19 menopausal women who sought treatment for climacteric symptoms (the study group) and 44 healthy menopausal women (the control group). Life stress was assessed using a life event method in which factor analysis extracted four ways that women cope with stress: avoidance-oriented coping, consultation-oriented coping, aggression-expression coping, and problem-solving coping. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Studies of midlife have also suggested that psycho-social stress is a significant correlate of symptom frequencies in Canada (Kaufert et al 1992), the UK (Kuh et al 1997), the U.S. (McKinlay et al 1987;Thurston et al 2008), Spain (Sievert et al 2007b), Japan (Igarashi et al 2000), and Chile (Binfa et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Studies of midlife have also suggested that psycho-social stress is a significant correlate of symptom frequencies in Canada (Kaufert et al 1992), the UK (Kuh et al 1997), the U.S. (McKinlay et al 1987;Thurston et al 2008), Spain (Sievert et al 2007b), Japan (Igarashi et al 2000), and Chile (Binfa et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately 75% of postmenopausal women and about 49% of perimenopausal women have experienced hot flashes that persist for 6 months to 5 years [3], while approximately 10% of women experience VMS as long as 12 years after the final menstrual period [4]. VMS have a significant impact on the quality of life and overall physical health, leading to treatment for these symptoms [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Psychopathology before menopause plays a role in the development of psychological symptoms during menopause and symptom severity. The biology of depression in menopausal women may be different from that of non-menopausal women; these differences may be related to the climacteric hormonal changes [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Problem-solving strategies and coping behaviour are decisive for improving the condition of the climacteric woman [10]. An avoidance-oriented coping style correlates positively with severity of symptoms [6]. …”
Section: Introductionmentioning
confidence: 99%